Competencies of Philippine Coast Guard Personnel in the Enforcement of Criminal Laws - Abanilla, Ailene G. (Future Science / FSH-PH Publications, 2024)
This study shows a comprehensive evaluation of the Philippine Coast Guard (PCG) personnel's competencies in enforcing maritime criminal laws. Anchored in the context of the Philippines' complex maritime environment, the research highlighted the pivotal role of the PCG in safeguarding maritime security, safety, and environmental protection through effective law enforcement. Employing mixed methods, the study used interviews and survey questionnaire among PCG personnel. The findings revealed significant gaps in knowledge and skills among PCG personnel, particularly in the application of specific criminal laws and procedures relevant to maritime law enforcement. It was observed that while personnel possessed basic knowledge of laws, there were inconsistencies in their ability to apply this knowledge effectively during law enforcement operations. Additionally, the study identified a strong correlation between the level of education, training, and the competency levels of the respondents, suggesting that continuous professional development and targeted training programs are crucial for enhancing the PCG’s operational effectiveness. The study underscored the need for a structured and comprehensive training program tailored to address the identified competency gaps. The program is essential for enhancing capabilities for maritime criminal laws enforcement. The research advocated for the integration of theoretical knowledge with practical application through continuous education and training, emphasizing the importance of developing a skilled workforce capable of adapting to the challenges of maritime law enforcement. The findings serve as a strategic guide for the PCG to enhance personnel management, operational efficiency, and stakeholder trust, ultimately contributing to the nation's maritime security framework.